Enterprise Risk Management pada Perguruan Tinggi Swasta (Studi Kasus di STMA Trisakti) - Syahrial, Syahrial Sidik (Program Studi Magister Manajemen Lingkungan, 2023)
The purpose of this paper is to analyse the implementation of risk management in higher education at Sekolah Tinggi Manajemen Asuransi Trisakti. The research method uses exploratory research design, because the purpose of this research is to understand the problems of risk management at STMA Trisakti. Data was obtained by conducting interviews and barinstorming with the head of the study programme, head of section, and Head of Centre, also by using secondary data, namely the number of students, number, lecturers, and other data. The stages of analysis are carried out through risk identification, risk assessment and evaluation, risk mitigation planning and data analysis and interpretation. Based on the results of risk identification, there are 7 inherent risks that can have a significant impact on the sustainability of STMA Trisakti. Based on the risk profile of the seven identified risks, risks 1 and 6 have a qualitative impact on reducing accreditation ratings, risks 2, 3 and 7 have an impact on not achieving performance targets, risks 4 and 5 can have an impact on reducing the National Higher Education clustering. Quantitative impact Risks 1, 2, 3 and 6 have an impact on institutional losses, risks 4, 5 and 7 have an impact on low budget absorption (cost centre). Some risks require handling in a short time such as risks 2, 4 and 7 can result in residual risk not in accordance with the expected risk target (risk appetite), so that continuous risk handling is needed. This study has limitations, namely risk identification is not carried out in depth in all work units. Future research is expected that risk identification is carried out in all work units in Higher Education, so that existing risks can be immediately mitigated and improvements made immediately. Keywords: Enterprise Risk Management, Universities